2018
DOI: 10.1128/aac.00864-18
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Novel Amino Acid Alterations in PmrA or PmrB to Colistin Resistance in mcr -Negative Escherichia coli Clinical Isolates, Including Major Multidrug-Resistant Lineages O25b:H4-ST131- H 30Rx and Non-x

Abstract: Colistin is a last-line drug for multidrug-resistant Gram-negative bacteria. We previously reported four plasmid-mediated colistin resistance () gene-negative colistin-resistant clinical isolates, including the major pathogenic and fluoroquinolone-resistant strains O25b:H4-ST131-30Rx (isolates SRE34 and SRE44; MIC for colistin = 16 mg/liter), non-x (SME296; MIC = 8 mg/liter), and O18-ST416 (SME222; MIC = 4 mg/liter). In this study, we investigated the colistin resistance mechanism and identified novel amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 27 publications
(51 reference statements)
1
44
2
1
Order By: Relevance
“…Because chromosomal mutations in basRS , but not in other regulatory systems, have previously been suggested to cause colistin resistance in E. coli (2428), we next aimed to establish the contribution of the basRS alleles in the colistin-resistant phenotype of these bloodstream isolates. Due to the multidrug-resistant nature of the clinical isolates (Figure 1C), we were unable to generate targeted mutations in these strains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because chromosomal mutations in basRS , but not in other regulatory systems, have previously been suggested to cause colistin resistance in E. coli (2428), we next aimed to establish the contribution of the basRS alleles in the colistin-resistant phenotype of these bloodstream isolates. Due to the multidrug-resistant nature of the clinical isolates (Figure 1C), we were unable to generate targeted mutations in these strains.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Sato et al . also exclusively found phosphoethanolamine-modified lipid A in colistin-resistant clinical E. coli isolates (24). The reliance of Escherichia on the modification of lipid A by phosphoethanolamine to acquire colistin resistance, suggests that the inhibition of this class of enzymes by blocking the conserved catalytic site (31) could be a target for future drug development and opens the possibility of combination therapy with colistin and an inhibitor of phosphoethanolamine transferase (63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, different pmrB and pmrA mutations ( Table 7) responsible for colistin resistance in E. coli were observed. 48,53,58 In Col R E. coli O25 isolated from human clinical specimens in Japan, deletion (Δ27-45, LISVFWLWHESTEQIQLFE) in pmrB and substitution (L105P) in pmrA were reported. 53 In the same study, substitution (G206D) was observed in pmrB in Col R E. coli O25 and O18 isolates.…”
Section: Discussionmentioning
confidence: 99%
“…48,53,58 In Col R E. coli O25 isolated from human clinical specimens in Japan, deletion (Δ27-45, LISVFWLWHESTEQIQLFE) in pmrB and substitution (L105P) in pmrA were reported. 53 In the same study, substitution (G206D) was observed in pmrB in Col R E. coli O25 and O18 isolates. 53 These mutations have led to modification of lipid A with the addition of PEtN and upregulation of eptA (pmrC) and arnT expression and thereby resistance to colistin.…”
Section: Discussionmentioning
confidence: 99%